Jaime Guzmán’s political thought in the civic education of the Chileans in dictatorship - Pérez Godoy, Fernando; Valencia Narbona, Loreto (Cuadernos de Historia, 2021)
The present paper researches the impact of Jaime Guzmán`s political thought on the civic education of the Chileans in dictatorship, specifically on the gestation of the Program of Civic Education of 1982. It claims that the building of school curriculum was made from four structural notions of his political ideology: Authority, Intermediate Society, Subsidiary State and Capitalism. It concludes with a reflect on the role of the ideologization of scholar programs, the instrumentalization of the history and its consequence on the civil education of the Chilean society.